AN ANALYSIS ON THE MEANING IN HOMBO BATU CULTURE IN BAWOMATALUO VILLAGE, TELUK DALAM - Adrianus Tafonao; Arining Wibowo; Maria G. Sri Ningsih (JURNAL ILMIAH BAHASA DAN SASTRA, 2015)
Hombo Batu is formed because in ancient times there was a war between villages. So that every village had to find a way to defend their village, one of which they did was to close each of their villages, ranging from bamboo which were made sharp as a spear as a form of defense. However, chiefs were also looking for the soldiers, who asked the youngsters to jump over the fence ranging from 4 meters, but because it was too high chieftain change the height to 2 meters so that the young people were able to jump over the fence then the commander will make them as soldiers. At the time, the form of the fence was also different, not like bamboo, but from stones that have been arranged as high as 2 meters. This study aims to analyze the original meaning of Hombo Batu culture itself, so that people know the true meaning in Hombo Batu culture. Researcher has some research problems, there are: the meaning of Hombo Batu culture, the functions of Hombo Batu culture, the factors which affect of the shifting in Hombo Batu culture, the effort of Bawomatoluo population to maintain the Hombo Batu culture. Data collection is done by field notes and interviews of heads of tribes, stone jumpers, and the people in the Bawomataluo village, to obtain the desired data. The data are taken from data in Hombo Batu culture, to analyze data the researcher use using triangulation method. In this study the researcher will use data triangulation and methodological triangulation. Methodological triangulation which refers to the use of more than one method for gathering data. Output obtained in the form of grouping the opinion of the society that shows whether it is the original meaning in Hombo Batu culture or not. The researchers concluded that the true meaning of Hombo Batu is as establishment of warriors to defend their villages, is not a requirement to get married. However, because this time the war between villages is no longer there, then Hombo Batu become one of the tourist places can be visited by anyone and from anywhere.